Determination of bioactivity of seed protein hydrolysates and amygdalin content for some apricot (Prunus armeniaca L.) varieties grown in Malatya, Turkey - Mutlu, Merve; Hayaloglu, Ali Adnan (FOOD ANALYTICA GROUP, 2022)
In this study, the aim was to determine the bioactivity of seed proteins from different apricot varieties, namely Hacıhaliloğlu (a PDO product protected by the EU), Hasanbey, Kabaaşı and Zerdali. Bioactivities of isolates obtained by precipitation at the isoelectric point of seeds and hydrolysates obtained by enzymatic hydrolysis with alcalase were examined. In terms of angiotensin converting enzyme (ACE)-inhibitory activity, isolate and hydrolysate from Kabaaşı variety showed the highest activity, while isolate from Hasanbey and hydrolysate from Zerdali had the lowest activity (P<0.05). Kabaaşı isolate and hydrolysate had the lowest antioxidant activity (P<0.05). The amount of amygdalin detected in sweet apricot seeds (Hacıhaliloğlu, Hasanbey, Kabaaşı) is below the toxic level specified by the EFSA. The results suggest that apricot seed protein may be a potential source of plant protein for human nutrition, especially for vegan consumers. Apricot seeds were also rich in terms of ACE-inhibitory and antioxidant activities. In this study, the aim was to determine the bioactivity of seed proteins from different apricot varieties, namely Hacıhaliloğlu (a PDO product protected by the EU), Hasanbey, Kabaaşı and Zerdali. Bioactivities of isolates obtained by precipitation at the isoelectric point of seeds and hydrolysates obtained by enzymatic hydrolysis with alcalase were examined. In terms of angiotensin converting enzyme (ACE)-inhibitory activity, isolate and hydrolysate from Kabaaşı variety showed the highest activity, while isolate from Hasanbey and hydrolysate from Zerdali had the lowest activity (P<0.05). Kabaaşı isolate and hydrolysate had the lowest antioxidant activity (P<0.05). The amount of amygdalin detected in sweet apricot seeds (Hacıhaliloğlu, Hasanbey, Kabaaşı) is below the toxic level specified by the EFSA. The results suggest that apricot seed protein may be a potential source of plant protein for human nutrition, especially for vegan consumers. Apricot seeds were also rich in terms of ACE-inhibitory and antioxidant activities.